DAMPAK BUDAYA ORGANISASI, BERBAGI PENGETAHUAN DAN TURBULENSI TEKNOLOGI DALAM MENINGKATKAN PERFORMANCE: INDUSTRI KREATIF DI INDONESIA - Piliang, Arfah; Nuraini, Nuraini; Wirdayani, Wirdayani; Tinaria, Lisa (Jurnal Daya Saing, 2024)
Abstract: This study aims to determine the relationship between technological turbulence, knowledge sharing, organizational culture, and creative industry performance in Indonesia. This research was conducted on the songket creative industry in Indonesia with a total sample of 328 respondents who are owners of the songket creative industry and their managers. This study uses the SEM-AMOS 24 measuring tool. The results show that organizational culture (BO) affects the creation of knowledge sharing behavior (BP) and organizational culture (BO) affects the creation of ideas to increase technological turbulence (TT). However, technology turbulence does not have an impact on improving performance and knowledge sharing also does not have an impact on increasing technology turbulence in organizations. Therefore, further research is needed that focuses on the dimension of technological turbulence and adds other capabilities such as open innovation. So that open innovation can have an impact on technological turbulence. The findings of this study should be a guide for managers who want to control factors that affect the company's capacity, especially the SME's creative industry.